Understanding the subjective experiences of memory concern and MCI diagnosis: A scoping review. (February 2023) - Carter, Christine; James, Tiffeny; Higgs, Paul; Cooper, Claudia; Rapaport, Penny
Introduction: Many older people experience memory concerns; a minority receive a diagnosis of Mild Cognitive Impairment (MCI) or Subjective Cognitive decline (SCD). There are concerns that medicalisation of MCI and memory concern may fail to acknowledge subjective experiences. Aim: We explore the meaning individuals give to their memory concerns, with or without a diagnosis of MCI and SCD. Method: We scoped literature exploring subjective experiences of memory concern, with or without a diagnosis of MCI or SCD. We searched CINAHL, PsycINFO and MEDLINE in March 2020, and updated in Sept 2021.We used (Arksey & O'Malley, 2005) framework to guide our scoping review method and thematic analysis to analyse our findings. Results: We screened 12, 033 search results reviewing the full texts of 92 papers. We included 24 papers, including a total of 453 participants, the majority of whom were female, from White ethnic majority populations (or from studies where ethnicity was not identified) with high levels of education. In 15 out of 24 studies, 272 participants were diagnosed with MCI. We identified two themes; Making a diagnosis personal and Remembering not to forget . We found that subjective experiences include normative comparison with others of the same age and responses including fear, relief, and acceptance, but culminating in uncertainty. Conclusion: Drawing upon sociology, we highlight the subjective experiences of living with memory concerns, SCD and an MCI diagnosis. We identify a gap between the intended purpose of diagnostic labels to bring understanding and certainty and the lived experiences of those ascribed them.